The physiological and activity demands experienced by Australian female basketball players during competition - Scanlan, A. T.; Dascombe, P. J.; Reaburn, P.; Dalbo, V. J. (Journal of Science and Medicine in Sport, 2012)
To describe the physiological and activity demands experienced by Australian female basketball players during competition.